Randomized Clinical Trial of a Sustained-Exposure Ciprofloxacin for Intratympanic Injection During Tympanostomy Tube Surgery. (February 2016) - Mair, Eric A.; Moss, Jonathan R.; Dohar, Joseph E.; Antonelli, Patrick J.; Bear, Moraye; LeBel, Carl
Objective: This exploratory clinical trial evaluated the safety and clinical activity of a novel, sustained-exposure formulation of ciprofloxacin microparticulates in poloxamer (OTO-201) administered during tympanostomy tube placement in children. Methods: Double-blind, randomized, prospective, placebo- and sham-controlled, multicenter Phase 1b trial in children (6 months to 12 years) with bilateral middle ear effusion requiring tympanostomy tube placement. Patients were randomized to intraoperative OTO-201 (4 mg or 12 mg), placebo, or sham (2:1:1 ratio). Results: Eighty-three patients (52 male/31 female; mean age, 2.80 years) were followed for safety (otoscopic exams, cultures, audiometry, and tympanometry) and clinical activity, defined as treatment failure (physician-documented otorrhea and/or otic or systemic antibiotic use ≥3 days post surgery). At baseline, 14.3% to 36.8% of children showed positive cultures of middle ear effusion samples in at least 1 ear. Through day 15, treatment failures accounted for 14.3%, 15.8%, 45.5%, and 42.9% of patients (OTO-201 4 mg, OTO-201 12 mg, placebo, and sham, respectively); treatment failure reductions for OTO-201 doses were significant compared to pooled control ( P values = .023 and .043, respectively). Observed OTO-201 safety profile was indistinguishable from placebo or sham. Conclusions: Results of this first clinical trial suggest that OTO-201 was well tolerated and shows preliminary clinical activity in treating tympanostomy tube otorrhea.